Promoting an Academic International Profile in Undergraduate Students of Psychology Programs in Colombia - Torres-Escobar, Germán Andrés; Correa-López, Rolan Arcadio (GIST – Education and Learning Research Journal, 2020)
The present reflective article aims to describe some challenges that psychology programs in Colombia must face in the future, in order to let their students achieve an international professional profile and to improve their academic quality. First of all, psychology programs need to implement a bilingual curriculum, with many basic and professional courses in a foreign language like English, to teach students to think social and psychological problems in a wide intercultural way (Coulson & Homewood, 2016; Taylor & Hulme, 2015). Secondly, psychology professors should motivate their students to acquire higher levels of engagement with bilingual communication learning, to have better opportunities of professional development by applying to academic exchange experiences with international universities.